Lugar, saúde e informação: os círculos de informação da atenção básica do SUS no contexto na disputa pelo conceito de saúde - Silva, Raphael Curioso Lima (2014)
Through the analysis of the informational activity at the primary care of SUS at the scale of places, this dissertation has as central objective to observe the dispute for the concepts of health and sickness, in the ambit of Brazilian Health Movement, featuring, on one hand, the clinic, biomedical or flexnerian line hegemonic, scientifically restrict and the primary frame of references for the Brazilian health politics and on the other hand a multiplicity of new proposals and critic thoughts to the current model, which have , as common characteristic, the worry with a territorial way of thinking the health context, therefore beyond the biological processes. On the first chapter we jut out with details these scientific and ideological movements, on a wider way, but also on the specificities of the public health s information politics. On the second chapter we analyze the downward health information circle at the basic care, observing the operational processes of the information s technical systems SIAB and e-SUS. On the third and last chapter, we give references to think about an upward health information circle, centered on the places, ruled by the notions of autonomy, organic solidarity and communicational density. It would possess, as method s primary horizon, the local organization of production and managing of information through the work of the Health Community Agent, privileging therefore the urgency of the most contingent needs of the people in theirs every day s life